2015
DOI: 10.1080/00405000.2015.1024974
|View full text |Cite
|
Sign up to set email alerts
|

Study of dyeing properties of wool fabrics treated with microwave

Abstract: Wool was pretreated with microwave and then dyed with Lanasol reactive dye and Palatin 1:1 metal complex dye by conventional exhaust dyeing process. Adsorption behaviour and diffusion coefficient were also studied. A higher dye uptake rate and increased diffusion coefficient of treated fibres are observed in the dyeing test after microwave pretreatment, but the adsorption behaviour remains constant. Microwave pretreatment has a slightly damaging effect on the surface scale-like structure of wool, which results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Microwave technology has only individually been used as an auxiliary method in some textile applications, such as dyeing, degumming and functional grafting, 24,25 but the application potential of MVD has not been paid enough attention. Some studies have shown that microwave irradiation could affect the surface roughness and aggregated structure of natural fibers, 26,27 and in our previous research, we have also characterized the performance of cashmere after microwave irradiation. 5,28 For cashmere, the influence of MVD on the mechanical properties of fibers should be paid special attention, it is the most important character of fibers in drying and even in the whole of cashmere processing.…”
mentioning
confidence: 90%
“…Microwave technology has only individually been used as an auxiliary method in some textile applications, such as dyeing, degumming and functional grafting, 24,25 but the application potential of MVD has not been paid enough attention. Some studies have shown that microwave irradiation could affect the surface roughness and aggregated structure of natural fibers, 26,27 and in our previous research, we have also characterized the performance of cashmere after microwave irradiation. 5,28 For cashmere, the influence of MVD on the mechanical properties of fibers should be paid special attention, it is the most important character of fibers in drying and even in the whole of cashmere processing.…”
mentioning
confidence: 90%
“…It's made out of the right sheep's skin, predominantly consisting of a diverse morphological structure of pro-steins (97 percent) and lipids (1 percent), [40] For wool fibers the scales onto the surface are the main cause of felting shrinkage and contribute to the directional frictional effect. [41] It is made of a protein called keratin generated in the process of α-amino acid biosynthesis. Wool fiber is formed from cell death.…”
Section: Wool Fibermentioning
confidence: 99%
“…To reduce wastewater discharges and environmental impacts, various methods were used to improve the exhaustion and fixation of dyes on wool fiber. These attempts included (a) pretreatment or modification of wool fiber before coloration [10,11,12,13,14,15,16]; (b) synthesis of novel dyestuffs [8,17]; (c) microencapsulation with liposomes [18,19]; (d) reuse of dyebath [20] and seawater [21]; (e) foam dyeing [22]; (g) ultrasound-assisted dyeing [23,24,25]; and (h) solvent-assisted dyeing using mixed solvent [26], supercritical critical fluid, and/or reverse micelle [27,28,29,30,31,32].…”
Section: Introductionmentioning
confidence: 99%